Understanding Opioid Prescribing Practices of Resident Physicians. Issue 5 (May 2023) - Coughlin, Julia M.; Terranella, Samantha L.; Ritz, Ethan M.; Xu, Thomas Q.; Tierney, John F.; Velasco, Jose M.; Myers, Jonathan A.
Background: To compare opioid prescribing practices of resident physicians across a variety of surgical and nonsurgical specialties; to identify factors which influence prescribing practices; and to examine resident utilization of best practice supplemental resources. Methods: An anonymous survey which assessed prescribing practices was completed by residents from one of several different subspecialties, including internal medicine, obstetrics and gynecology, general surgery, neurosurgery, orthopedic surgery, and urology. Fisher's exact test assessed differences in prescribing practices between specialties. Results: Only 35% of residents reported receiving formal training in safe opioid prescribing. Overall, the most frequently reported influences on prescribing practices were the use of standardized order sets for specific procedures, attending preference, and patient's history of prescribed opioids. Resident physicians significantly underutilize best practice supplemental resources, such as counseling patients on pain expectations prior to prescribing opioid medication; contacting established pain specialists; screening patients for opioid abuse; referring to the Prescription Monitoring Program; and counseling patients on safe disposal of unused pills ( P < .001). Discussion: The incorporation of comprehensive prescribing education into resident training and the utilization of standardized order sets can promote safe opioid prescribing.